PENGARUH DISIPLIN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. RADIO SOLOK CITRA NADANUSA DI KABUPATEN SOLOK - hane johan (STKIP Pesisir Selatan, 2019)
The problem raised in this study was the performance of employees at Solok Citra Nadanusa Radio in Solok Regency, the research variables were discipline, job satisfaction and employee performance. This study aims to reveal (1) the influence of discipline on employee performance, (2) the effect of job satisfaction on employee performance, (3) the effect of discipline and job satisfaction together on employee performance. Based on observations and studies of experience, researchers found that employee performance at Radio Solok Citra Nadanusa in Solok District was still not satisfactory (still low). Researchers suspect that the low performance of employees is caused by many factors, among others, less wise leadership and compensation that is less satisfactory / not in accordance with his job. To answer this problem there are three hypotheses the researcher proposes. Pentama; there is an influence of discipline on employee performance, Second; there is an influence of job satisfaction on employee performance, Third; there is the influence of discipline and concurrent job satisfaction on employee performance. The population of this study were all employees at Solok Citra Nadanusa Radio in Solok Regency. The sample in this study was taken part of the population as many as 30 people. Data was collected using a Likert Scale model questionnaire. Then the data were analyzed using correlation and regression techniques with the help of the SPSS for Windows version 13.00 computer program. The results of the analysis show that there are disciplinary contributions to 87.2% employee performance and contribution to job satisfaction on employee performance 81.5%. While the contribution of discipline and job satisfaction simultaneously on employee performance amounted to 89.3%. When viewed the effect on the regression equation is Y = 19.988 + 0.595 X1 + 0.287 X2 Based on the results of these studies, the researchers concluded that there is a significant effect of discipline and job satisfaction together on employee performance. So the authors suggest to the parties concerned to enforce discipline and pay attention to employee compensation, so that employee performance is better or significantly increased. This does not mean that other factors, such as work motivation, educational opportunities, career system, promotion, work discipline, infrastructure, climate and work culture, security and protection of work that are not examined are ignored.